Public Theology in an Age of World Christianity - Chung, P. author. aut Link
VIII, 268 p.
Keywords: This book aims to rearticulate and reinterpret a Christian concept of God's mission and evangelization in light of the universal, irregular, and transversal horizon of God's narrative as it pertains to the realities of public sphere.